Vasculature Remodeling in a Rat Model of Cerebral Ischemia. The Fate of the BrdU-Labeled Cells Prior to Stroke - Surugiu, Roxana; Glavan, Daniela; Popescu, Mircea; Margaritescu, Otilia; Eugen, Radu; Popa-Wagner, Aurel (Frontiers in Neurology, 2018)
Despite the obvious clinical significance of post-stroke angiogenesis, a detailed microscopic analysis of pre-stroke vascular remodeling and post-stroke angiogenesis has not yet been undertaken in an experimental model. In this study, using BrdU-labelling of proliferating cells and immunofluorescence of pre- and post-stroke rats, we found that (i) BrdU administered before stroke was incorporated preferentially into the nuclei of endothelial cells lining the lumen of existing blood vessels and newly born neurons in the dentate gyrus but not in the subventricular zone or proliferating microglia. (ii) BrdU injection prior stroke led to the patchy distribution of newly incorporated endothelial cells in existing blood vessels of the adult rat brain. (iii) BrdU injection prior stroke specifically labelled neuronal precursors cells in the region beyond the inhibitory scar region which seems to be permissive to regenerative events. (iv) BrdU injection after stroke led to the labelling of endothelial cells crossing or detaching from the disintegrating blood vessels, and their incorporation into new blood vessels in the stroke region, scar tissue and the region beyond. (v) BrdU injection after stroke led to the specific incorporation of BrdU+ nuclei into the “pinwheel” architecture of the ventricular epithelium. (vi) Blood vessels in remote areas of the infarct core and in the contralateral non-lesioned cortex, showed co-labelled BrdU/RECA+ endothelial cells shortly after the BrdU injection, which strongly suggests a bone marrow origin of the endothelial cells. In the damaged cortex, a BrdU/P4Hß double labeling in close proximity of collagen IV-labelled basement membrane suggests that, in addition to bone marrow derived endothelial cells, the disintegrating vascular wall itself could also be a source of proliferating endothelial cells. (vii) By day 28 after the stroke, new blood vessels were emerging in the perinfarcted area and the scar tissue region, which is generally resistant to regenerative events. Finally, beyond the inhibitory fibrotic scar, in a region of soft tissue that we dubbed “islet of regeneration”, vigorous angiogenesis was also detected. Conclusion: BrdU administered before and after stroke allows the detection of specific brain vasculature remodelling.